2013
DOI: 10.1371/journal.pone.0070216
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of FKBP5 Genetic Variation to Gemcitabine Treatment and Survival in Pancreatic Adenocarcinoma

Abstract: PurposeFKBP51, (FKBP5), is a negative regulator of Akt. Variability in FKBP5 expression level is a major factor contributing to variation in response to chemotherapeutic agents including gemcitabine, a first line treatment for pancreatic cancer. Genetic variation in FKBP5 could influence its function and, ultimately, treatment response of pancreatic cancer.Experimental DesignWe set out to comprehensively study the role of genetic variation in FKBP5 identified by Next Generation DNA resequencing on response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Thus, FKBP51 positively regulates melanoma stemness and metastatic potential (Romano et al., 2013). FKBP51 is thought to be a key factor in the progression and chemotherapeutic response of pancreatic adenocarcinoma (Ellsworth et al., 2013), and it is close‐related to acute lymphoblastic leukemia and several variants of breast, ovary and lung tumor pathologies (Romano et al., 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, FKBP51 positively regulates melanoma stemness and metastatic potential (Romano et al., 2013). FKBP51 is thought to be a key factor in the progression and chemotherapeutic response of pancreatic adenocarcinoma (Ellsworth et al., 2013), and it is close‐related to acute lymphoblastic leukemia and several variants of breast, ovary and lung tumor pathologies (Romano et al., 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have investigated the FKBP5 locus by using a tagging approach to investigate variants that best cover the genetic diversity in different populations, but recently next‐generation sequencing projects that catalog all variants in this gene, including rare and private variants, have been described (Ellsworth et al 2013a,b; Pelleymounter et al ). The best investigated and characterized polymorphisms are within a haplotype spanning the whole gene (in Caucasians from the promoter area to the 3′UTR and in Africans from intron 1 to the 3′UTR) that is tagged by rs3800373, rs9296158 or rs1360780 and contains up to 18 single nucleotide polymorphisms (SNPs) in strong linkage disequilibrium in Caucasians (when mapped to the 1000 genomes next‐generation sequencing project using r 2 threshold of 0.8 and distance of 500 kb).…”
Section: Genetic Variants In Fkbp5mentioning
confidence: 99%
“…Crucially, we demonstrated cross‐trial replication of prediction performance across rating scales in both STAR*D (QIDS‐C scale) and ISPC (HDRS scale) trials with precision similar to that observed in training with PGRN‐AMPS data. This work also represents an advance over traditional pharmacogenetic candidate gene approaches that identify plausible genes and SNPs associated with outcomes . We achieved that advance by asking whether the application of machine‐learning approaches that combine clinical assessments with a group of functionally validated pharmacogenomic SNPs as predictor variables might make it possible to predict SSRI treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%